2018
DOI: 10.2478/botlit-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Folk medicine used for the treatment of gynaecological disorders in rural areas of Bhadrak district, Odisha, India

Abstract: Panda T., Mishra N., Rahimuddin S., Pradhan B.K., Rout S.D., Mohanty R.B., 2018: Folk medicine used for the treatment of gynaecological disorders in rural areas of Bhadrak district, Odisha, India. -Botanica, 24(2): 132-142.Folk knowledge of the people in a given community has developed over time and is based on experience often tested over centuries of use, adapted to the local culture and environment and held by individuals or communities. This knowledge on resource utilization by human beings for medicinal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Similarly, Balamurugan et al (2018) [16] and Panda et al (2018) [17] reported the same findings. Indigenous peoples across the studied area depend closely on palms for food and construction material.…”
Section: Resultssupporting
confidence: 53%
“…Similarly, Balamurugan et al (2018) [16] and Panda et al (2018) [17] reported the same findings. Indigenous peoples across the studied area depend closely on palms for food and construction material.…”
Section: Resultssupporting
confidence: 53%
“…(Krishnaveni et al, 2020). The natural fibre that is taken from the palmyra palm is used for construction of thatched homes, baskets, winnowing fans (Kula), and fences (Panda et al, 2018).…”
Section: Traditional Uses Of Palm Treementioning
confidence: 99%
“…The natural food coloring substance can be extracted from matured ripe husk or mesocarp of palmyra (Selvakumar and Thanapaul, 2020). Also the palmyra is used for production of chemicals such as pectin, cellulose, hemicelluloses, pentosan-polysulfates, polyphenols, and lignin from the paste of male inflorescence (Balamurugan et al, 2018;Panda et al, 2018). The community of "Chamar" members extracts the sap from the male flower to make a fermented alcoholic beverage known as "Tadi".…”
Section: Traditional Uses Of Palm Treementioning
confidence: 99%
See 2 more Smart Citations